The roles of financial literacy and overconfidence in investment decisions in Saudi Arabia - Seraj, Abdullah Hamoud Ali; Alzain, Elham; Alshebami, Ali Saleh (Frontiers in Psychology, 2022)
Financial literacy has gained much attention among scholars, policymakers and other stakeholders due to its role in backing up investment decisions, improving personal financial management and increasing financial wellbeing. This study examines the influence of financial literacy on investment decisions with the moderating effect of the overconfidence behavioural bias. Data were collected from 180 respondents in Saudi Arabia using a questionnaire, and a convenience sampling technique was applied. The study’s findings were analysed using the partial least squares structural equation modelling (PLS-SEM) technique. It was found that financial literacy positively and significantly influenced investment decisions. Moreover, the results show that overconfidence positively affected investment decisions and that the relationship between financial literacy and investment decisions was positively and significantly moderated by overconfidence.